2001
DOI: 10.1007/s005350170063
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis associated with antiphospholipid syndrome

Abstract: Portal vein thrombosis is a rare occurrence, and often an underlying hypercoagulable state can be found. Recently, there has been growing interest and recognition of the antiphospholipid syndrome in association with acquired hypercoagulable state. This syndrome consists of the association of lupus anticoagulant or antiphospholipid antibodies with arterial or venous thrombosis, thrombocytopenia, and spontaneous abortion. We report a case of portal vein thrombosis associated with the antiphospholipid syndrome. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…The human β2GPI molecule, a plasma protein, has anticoagulant properties in vitro which are inhibition of prothrombinase activity, ADP-induced platelet aggregation, and platelet factor IX production [8]. Most previous reports showed a high prevalence of arterial thrombosis, while portal vein thrombosis in APS has been less commonly reported and these cases were not combined infections, unlike the present case [13]. Portal vein thrombosis can occur in intra-abdominal infections, as pancreatitis, cholangitis, portal vein phlebitis and intra-abdominal abscess.…”
Section: Case Reportcontrasting
confidence: 42%
“…The human β2GPI molecule, a plasma protein, has anticoagulant properties in vitro which are inhibition of prothrombinase activity, ADP-induced platelet aggregation, and platelet factor IX production [8]. Most previous reports showed a high prevalence of arterial thrombosis, while portal vein thrombosis in APS has been less commonly reported and these cases were not combined infections, unlike the present case [13]. Portal vein thrombosis can occur in intra-abdominal infections, as pancreatitis, cholangitis, portal vein phlebitis and intra-abdominal abscess.…”
Section: Case Reportcontrasting
confidence: 42%
“…Today, the PVT etiology is considered multifactorial, with association of prothrombotic and local trigger factors found even in the pediatric age group (6,10,21,23,29,33,34,37,47,52,53) . The causes of PVT may be grouped into three categories: direct injury of the portal vein with subsequent thrombus formation; vascular malformation which includes stenosis or even atresia of the portal vein; and hypercoagulable conditions which favor the thrombus formation (6,15,19,22,39,49,50,52) . Cases that do not fit in these groups are denominated as idiopathic PVT and, due to the great percentage of these cases, recent studies, mainly in adults, have focused on the evaluation of new etiological factors (7,16,17,22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…The causes of PVT may be grouped into three categories: direct injury of the portal vein with subsequent thrombus formation; vascular malformation which includes stenosis or even atresia of the portal vein; and hypercoagulable conditions which favor the thrombus formation (6,15,19,22,39,49,50,52) . Cases that do not fit in these groups are denominated as idiopathic PVT and, due to the great percentage of these cases, recent studies, mainly in adults, have focused on the evaluation of new etiological factors (7,16,17,22,23) . In the pediatric age group, the few available literature has been demonstrating that approximately 50% of the cases still remained with an unknown etiology (1,2,20,53) .…”
Section: Discussionmentioning
confidence: 99%
“…13 It has also been reported that portal vein thrombosis often develops as a result of APS. [14][15][16] In the current case, portal hypertension seemed to be induced by portal vein thrombosis, which was possibly caused by APS that slowly developed 5 years after the onset of BCC. Irregular distribution of pulmonary circulation might be also associated with APS.…”
Section: Discussionmentioning
confidence: 84%